Contributions of the sociology of childhood: addressing the look - Patrícia Demartini (Universidade Federal de Santa Catarina, 2002)
This text aims to bring some thoughts on the discussion of the sociology of childhood and raises some methodological considerations on trends in research seeking children as social actors. It interlocutions result of the special seminar held in the program offered to students for graduate education in the UFSC, which had the participation of Professor Dr. Manuel Sarmento (Universidade do Minho-Portugal), the professor Dr. Jucirema Quinteiro (Ced-UFSC) of Professor Dr. Nadir Zago (UFSC) and Professor Dr. Maurício da Silva (UFSC), under the coordination of Prof.. Dr. Joshua João da Silva Filho. Initially text search in this survey of the contributions of studies in English and in French a grant to the discussion on the emergence of the sociology of childhood, retrieving the current discussion about childhood and the need to build this area of study.